Gestión Ambiental Turística, para el Grand Victoria Boutique Hotel de la ciudad de Loja - Gaona Paccha, Jhon Franco (2024)
An Environmental Management System (EMS) allows minimizing the impacts generated from activities carried out in an establishment; for this reason the present research was proposed with the general objective: “To design an Environmental Management System for Tourism, to ensure responsible environmental performance in the Grand Victoria Boutique Hotel in the city of Loja”, and the specific objectives were: “To identify the environmental impacts generated in the Grand Victoria Boutique Hotel in the city of Loja” and “To propose an Environmental Management System for Tourism for the Grand Victoria Boutique Hotel in the city of Loja”. The first objective used the Duarte Environmental Impact Assessment methodology, considering: identification of activities carried out, environmental factors affected, identification of environmental impacts and environmental impacts assessment, in addition to apply surveys to guests to determine their environmental behavior. The second objective was based on International Standard ISO 14004. The results showed that the hotel generates 101 environmental impact, of which 40 are positive and 61 are negative; the environmental factors affected are water, soil, and air; and the service that generate environmental impacts are: lodging, food, spa, gym, recreation, and the warehouse area. Thus, the EMS is focused on mitigating impacts with measures such as: installing MiFare energy savers; incorporating solar panels; using recyclable and reusable packaging; among others. Finally, it is concluded that an EMS would bring benefits not only to the environment, but also to the hotel’s operations and image, attracting environmentally conscious clients and generating long-term savings.